How Mediterranean winegrowers perceive climate change - Angelina De Pascale; Carlo Giannetto; Agata Zirilli; Angela Alibrandi; Maurizio Lanfranchi (AIMS Agriculture and Food, 2023)
Farmers are the most affected by the negative impacts of climate change and, at the same time, are called upon to adapt to climate change. Despite this, the degree of perception and adaptive attitude of farmers to climate change is still quite limited, especially in smallholder family farms in the Mediterranean areas. This study explores the level of perception of climate change by PDO (Protected Designation of Origin) winegrowers in a region of southern Italy (Sicily) and the adaptation actions able to cope with climate change, using a nonparametric approach. The analysis is based on data collected through self-administered questionnaires submitted to 380 PDO winegrowers. For variables comparison the Mann Whitney and the Kruskall Wallis test were applied according to the number of compared samples (two or more independent samples, respectively). Results show how winegrowers' perceptions of climate change tends to vary according to age and education of the respondents and to altitude and size of vineyards. This study highlights how information and dissemination of knowledge among winegrowers play a strategic role in the perception of climate change, especially in rural and remote Mediterranean areas.